Habitat Specificity Modulates the Response of Small Mammals to Habitat Fragmentation, Loss, and Quality in a Neotropical Savanna - Mattos, Ingrid de; Zimbres, Bárbara; Marinho-Filho, Jader (Frontiers in Ecology and Evolution, 2021)
Landscape conversion of natural environments into agriculture and pasture are driving a marked biodiversity decline in the tropics. Consequences of fragmentation might depend upon habitat amount in the landscape, while the quality of remnants can also affect some species. These factors have been poorly studied in relation to different spatial scales. Furthermore, the impacts of these human-driven alterations may go beyond species loss, possibly causing a loss of ecosystem function and services. In this study, we investigated how changes in landscape configuration (patch size and isolation), habitat loss (considering a landscape gradient of 10, 25, and 40% of remnant forest cover), and habitat quality (forest structure) affect small mammal abundance, richness, taxonomic/ functional diversity, and species composition in fragmented landscapes of semideciduous forests in the Brazilian Cerrado. Analyses were performed separately for habitat generalists and forest -specialists. We live-trapped small mammals and measured habitat quality descriptors four times in 36 forest patches over the years 2018 and 2019, encompassing both rainy and dry seasons, with a total capture effort of 45,120 trap-nights. Regression analyses indicated that the effect of landscape configuration was not dependent on the proportion of habitat amount in the landscape to determine small mammal assemblages. However, both patch size and habitat loss impacted different aspects of the assemblages in distinct ways. Smaller patches were mainly linked to an overall increase in small mammal abundance, while the abundance of habitat generalists was also negatively affected by habitat amount. Generalist species richness was determined by the proportion of habitat amount in the landscape. Specialist richness was influenced by patch forest quality only, suggesting that species with more demanding habitat requirements might respond to fragmentation and habitat loss at finer scales. Taxonomic or functional diversity were not influenced by landscape structure or habitat quality. However, patch size and habitat amount in the landscape were the major drivers of change in small mammal species composition in semideciduous forests in the Brazilian savanna.